Changes in numbers and habitat utilization of wintering Whooper Swans Cygnus cygnus in Sweden 1964—1977 - Nilsson, Leif (Ornis Svecica, 1997)
A country-wide survey of wintering Whooper Swans Cygnus cygnus was undertaken in south Sweden in January 1995 as part of an international census of the species. The paper reports on this census and analyses Whooper Swan counts from earlier International Waterfowl Census data to elucidate changes in numbers and habitat utilization of the swans. A marked increase in the number of Whooper Swans was found between the first country-wide surveys in the early 1970s and 1995, when the winter population was estimated to be at least 8,000. The increase is not reflected in the midwinter indices, calculated from the International Waterfowl Census data, due to an increasing tendency of the Whooper Swans to feed on land in the southernmost part of the country. In January 1995, nearly 60% of the Whooper Swans in Scania were found on fields, mainly rape and winter wheat, whereas in the other parts of the country the majority of swans still utilised water areas. Earlier in the season the Whooper Swans in Scania also used sugar beet spill for feeding. The field-feeding habit started in the 1970s.